2010
DOI: 10.1007/s11244-009-9438-3
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts for Selective Hydrocarbon Combustion in the Presence of CO

Abstract: Selective oxidation of hydrocarbons in the presence of CO goes against the relative reactivity of alkanes and CO. With the help of high throughput experimentation and hit amplification by selection, composition optimization and doping it was possible to develop new Cr-based mixed oxides, which selectively oxidize propane in the presence of CO. Heat of reaction, monitored by emissivity corrected IR-thermography, was chosen as screen, while conventional gas phase catalysis with product analysis by sensors was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…This number shows that the reaction is catalytic under all circumstances. In our previous publications, it was shown that with a Pt/Rh/Al 2 O 3 catalyst under our standard reaction conditions, conversions of CO of 90% and propane of 60% have been obtained at 350°C, comparable to our best mixed oxide catalysts [7][8][9]. Catalyst stability had been tested with a Ti 50 Cr 30 Ce 20 O x catalyst for 7 days at 350°C with no significant loss of activity [7].…”
Section: Catalyst Improvementmentioning
confidence: 52%
See 3 more Smart Citations
“…This number shows that the reaction is catalytic under all circumstances. In our previous publications, it was shown that with a Pt/Rh/Al 2 O 3 catalyst under our standard reaction conditions, conversions of CO of 90% and propane of 60% have been obtained at 350°C, comparable to our best mixed oxide catalysts [7][8][9]. Catalyst stability had been tested with a Ti 50 Cr 30 Ce 20 O x catalyst for 7 days at 350°C with no significant loss of activity [7].…”
Section: Catalyst Improvementmentioning
confidence: 52%
“…Since the oxygen content of such mixed oxides depends on O 2 partial pressure, synthesis recipe, precursors and calcination temperature as well as on feed gas composition and reaction temperature, the oxygen content of the catalysts used here is not specified, while the content of the metal ions is given as at.% of the overall cation content due to the amount used in synthesis. Among the above 5 starting oxides, Ti 62.5 Cr 37.5 O x had the highest activity with propane conversion of 39% at 350°C (42% in [7] confirms the reproducibility). The variation in synthesis parameters led to a slight increase in activity.…”
Section: Catalyst Improvementmentioning
confidence: 53%
See 2 more Smart Citations
“…A simple strategy of the catalyst design is provided by the directed evolution concept, which was applied to the development of noble-metal-free catalysts for the selective oxidation of CO in the presence of hydrogen [39]. Other successful examples are the development of hydrocarbon-selective oxidation catalysts in the presence of CO [40] and of CO-selective methanation catalysts in the presence of CO 2 [41]. Over the last 15 years, numerous sol-gel based recipes for a broad variety of compositions have been formulated by our group and summarized in the review [42].…”
Section: T Tammann Is 210mentioning
confidence: 99%